Picky eating and risk factors in children [Çocuklarda seçici yeme ve risk faktörleri] - (:unkn) unknown (Galenos Yayincilik,, 2018)
Picky eating is one of the common feeding problems in childhood. It consists of a combination of various eating behaviors, characterized by the rejection of both familiar and novel foods, strong food preference, inadequate amounts or variety of food consumption. Temporary or mild picky eating behaviors can be seen as a part of normal development. However, picky eating in early childhood may in some cases be a predictor of avoidant/restrictive eating disorders. Picky eating behaviors have the potential to adversely affect food consumption in children, diet quality, normal growth and future health outcomes. It is important to determine the risk factors for picky eating when picky eating behaviors that are common in early childhood can persist in school years and even in adulthood, and negative health outcomes are taken into consideration. Most picky eating behaviors can be corrected without any intervention. However, nutrition education should be given to both parents to improve their knowledge of child nutrition and to reduce their anxiety. In this review article, assessment methods used in current studies, the prevalence of picky eating, characteristics of nutrient intake and risk factors affecting development and approach to picky eating were examined. © 2018, Galenos Yayincilik,. All rights reserved.
Keywords: Child; Feeding problems; Food preference; Picky eating